MANAJEMEN BENCANA BANJIR OLEH BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DI KOTA TANGERANG - Bela Santika; Agus Sjafari (NIAGARA Scientific Journal, 2025)
The focus of this research is Flood Disaster Management in Tangerang City which occurs every year with an impact on property losses and impacts on the community. In its implementation, there are still several obstacles such as the lack of supervision of illegal buildings that increase the risk of flood disasters, there is no special early warning system for flood disasters, the limited personnel of the BPBD Pusdalops, the limited infrastructure facilities owned by the Tangerang City BPBD, and the lack of assistance to repair the houses of flood victims. The purpose of this study is to find out how flood disaster management by using Ramli (2010: 31 – 38) theory with descriptive qualitative research methods. Data collection was carried out by observation, interviews, and documentation. The results of the study show that the disaster management carried out by the Tangerang City BPBD is still not optimal. This study provides recommendations for building supervision, infrastructure management, reducing the risk of repeated flood disasters, and increasing community socialization.